Pengaruh Dropshipping terhadap Minat Usaha Online Mahasiswa STAI At-Tahdzib Jombang - Asyarurahim; Aulia, Reza Izzatun Nuril (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Backgound. Digital technology is a transition from its operation which no longer uses much human labor. The rapid development of digital technology is marked by the emergence of various cutting-edge communication tools, where everyone can manage, produce, and send and receive services anywhere and anytime without knowing the limitations of space and time Aim. Based on the limits and identification of predetermined problems, the problem formulation is: How Does Dropshipping Affect the Online Business Interest of STAI At-Tahdzib Jombang Students? Methods. The problem approach used in this study is to use quantitative survey research. Quantitative methods as research methods used to research on certain populations or samples, data collection using research instruments Results. From the results of the data analysis above, there are several results that show positivity and significance between variable (X) and variable (Y), therefore it can be seen that in the instrument validity test of 54 questionnaires that have been filled out are said to be valid because the calculation results using SPSS 22 state that the calculation > rtable. And in the instrument reliability test there are also results that show Cronbach's Alpha between 0.4-0.7 with variable values (X) 0.483 and variable (Y) 0.703, which is said to be reliable enough for questionnaires submitted to respondents. Keywords: Dropshipping, Online Business, Technology